Análisis del sistema lean construcción como herramienta para la mejora continua en la productividad de la Empresa Constructura Kuman para el Proyecto Torres de Altiva. (2022)
The construction sector has been preceded by different changes in recent decades, in favor of improving technical and technological processes, productivity, the conservation of environmental resources and sustainability. However, this growth has not evolved in Colombia, where we find many construction companies working in a traditional way or implementing the industrialized system without any efficiency in the terms and cost of the projects. In this monograph, a comparative analysis was carried out between the industrialized system and the implementation of the Lean Construction System, in Construtora Kuman, evaluating the tools of the operations and productivity management system.